Interconnected Set of Enzymes Provide Lysine Biosynthetic Intermediates and Ornithine Derivatives as Key Precursors for the Biosynthesis of Bioactive Secondary Metabolites - Paloma Liras; Juan Francisco Martín (Antibiotics, 2023)
Bacteria, filamentous fungi, and plants synthesize thousands of secondary metabolites with important biological and pharmacological activities. The biosynthesis of these metabolites is performed by networks of complex enzymes such as non-ribosomal peptide synthetases, polyketide synthases, and terpenoid biosynthetic enzymes. The efficient production of these metabolites is dependent upon the supply of precursors that arise from primary metabolism. In the last decades, an impressive array of biosynthetic enzymes that provide specific precursors and intermediates leading to secondary metabolites biosynthesis has been reported. Suitable knowledge of the elaborated pathways that synthesize these precursors or intermediates is essential for advancing chemical biology and the production of natural or semisynthetic biological products. Two of the more prolific routes that provide key precursors in the biosynthesis of antitumor, immunosuppressant, antifungal, or antibacterial compounds are the lysine and ornithine pathways, which are involved in the biosynthesis of β-lactams and other non-ribosomal peptides, and bacterial and fungal siderophores. Detailed analysis of the molecular genetics and biochemistry of the enzyme system shows that they are formed by closely related components. Particularly the focus of this study is on molecular genetics and the enzymatic steps that lead to the formation of intermediates of the lysine pathway, such as α-aminoadipic acid, saccharopine, pipecolic acid, and related compounds, and of ornithine-derived molecules, such as N5-Acetyl-N5-Hydroxyornithine and N5-anhydromevalonyl-N5-hydroxyornithine, which are precursors of siderophores. We provide evidence that shows interesting functional relationships between the genes encoding the enzymes that synthesize these products. This information will contribute to a better understanding of the possibilities of advancing the industrial applications of synthetic biology.